CIWIDEY VALLEY RESORT TOURISM OBJECT DEVELOPMENT AS DETERMINANT OF INCREASING TOURIST VISITS - Supriatna Supriatna; Haryono Sudriamunawar; Waluyo Zulfikar (Universitas Pasundan, 2020)
Ciwidey Valley Resort which is Tirta Tourism located in Ciwidey Tourism Area Precisely on KM.17 Road Barununggal Rancabali Bandung Regency, West Java is an artificial Tourism Area built in 2015 provides complete facilities for tourists who want to visit tourist locations including water warm water park, play ground, unique lodging, camping ground and ciwidey valley restaurant. The aim of this research is to find out how to develop Ciwidey Valley attractions in an effort to increase tourist arrivals that have an impact on Ciwidey Valley managers' income and regional budget revenues.The methods used by researchers in this study include descriptive analysis with a qualitative approach. Researchers use the development model according to Syamsu (2011) While the data collection techniques that the authors use in this study are the study of literature / documentation, observation, and interviews. Whereas the data validity technique uses triangulation.The initial step taken is to analyze the internal and external environment to find out how the service efforts provided in carrying out services and processes in carrying out tasks in the implementation of work processes. After that researchers also analyzed by interviewing with informants who have been determined previously to find out how the service and how the process of service provided by all workers in Ciwidey Valley Resort to visitorsThis research can be concluded by the researchers, that in an effort to increase the number of tourist arrivals by developing several tourist attractions supported by improving services but not all are optimal.